2011
DOI: 10.1183/09031936.00164410
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory health and endotoxin: associations and modification byCD14/-260 genotype

Abstract: Exposure to endotoxin has been associated with increased respiratory symptoms and decrements in lung function in occupational settings but little is known about the health effects of domestic exposure in adults. Here, we describe the association of respiratory disease, immunoglobulin (Ig)E sensitisation, bronchial reactivity and lung function with mattress endotoxin levels in adults, and determine whether these associations are modified by polymorphisms in CD14.Endotoxin levels in mattress dust from a populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…In other epidemiological studies, endotoxin, a component of the bacterial cell wall of mostly gram-negative bacteria [ 33 ] has been widely used as a proxy for bacterial exposure in settled dust. In a previous ECRHS investigation among the same study participants, there was no evidence of an association between exposure to endotoxin levels in mattress dust and the asthma score, however, an association with lung function might be modified by CD14 genotype [ 19 ]. A nationwide study of more than 2500 adult subjects in the U.S. (the National Survey of Allergens in Housing (NSLAH)), reported that increased exposure to endotoxin from bedding was most strongly associated with wheezing ever, wheezing in the past month and within the past year in adjusted analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other epidemiological studies, endotoxin, a component of the bacterial cell wall of mostly gram-negative bacteria [ 33 ] has been widely used as a proxy for bacterial exposure in settled dust. In a previous ECRHS investigation among the same study participants, there was no evidence of an association between exposure to endotoxin levels in mattress dust and the asthma score, however, an association with lung function might be modified by CD14 genotype [ 19 ]. A nationwide study of more than 2500 adult subjects in the U.S. (the National Survey of Allergens in Housing (NSLAH)), reported that increased exposure to endotoxin from bedding was most strongly associated with wheezing ever, wheezing in the past month and within the past year in adjusted analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The (1,3)-ß-D-glucan inhibition EIA makes use of affinity-purified polyclonal rabbit antibodies, and with the algae-derived glucan laminarin as the coated antigen and the calibration standard, as described previously [ 25 ]. For the current investigation, only the results of the (1,3)-ß-D-glucan measurements will be considered in relation to health, as results on endotoxin have been published previously [ 19 ]. However, endotoxin will be included, investigating the correlation between different microbial parameters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, an increasing number of studies have examined the relationship between CD14 gene variations and disease susceptibility. It has been reported that the -159 C/T variant in the CD14 gene plays an important role in regulating CD14 expression and is associated with the susceptibility to various diseases, including allergies (Sengler et al, 2003;Bakolis et al, 2012;Wang et al, 2012). Previous studies focused on the association between atopic asthma and CD14 gene variations (Kedda et al, 2005;Nishimura et al, 2006;Zhao et al, 2011), but the results are contradictory.…”
Section: Introductionsmentioning
confidence: 86%
“…The study of CD14 as a modifier of the effects of endotoxin on allergy‐related outcomes is an excellent example for why interaction should be studied . Interactions between the level of endotoxin and CD14 polymorphisms have been reported to relate to total IgE levels , lung function , eczema and sensitization . The current work extends this successful approach to the investigation of non‐genetic factors, and the results suggest that it is an approach that needs continued application in allergic disease research.…”
Section: Discussionmentioning
confidence: 99%